A review of the jumping plant-lice (Hemiptera: Psylloidea) of the Canary Islands, with descriptions of two new genera and sixteen new species - Bastin, Saskia; Burckhardt, Daniel; Reyes-Betancort, J. Alfredo; Hernández-Suárez, Estrella; Ouvrard, David (Zootaxa, 2023)
The psyllid fauna of the Canary Islands is reviewed on the basis of recent field work on Tenerife, La Gomera, La Palma Gran Canaria and Lanzarote, as well as the examination of material deposited in several collections. Two new genera and 16 new species are described: Drepanoza Bastin, Burckhardt & Ouvrard gen. nov., Percyella Bastin, Burckhardt & Ouvrard gen. nov., Agonoscena atlantica Bastin, Burckhardt & Ouvrard sp. nov., A. sinuata Bastin, Burckhardt & Ouvrard sp. nov., Arytaina meridionalis Bastin, Burckhardt & Ouvrard sp. nov., Cacopsylla crenulatae Bastin, Burckhardt & Ouvrard sp. nov., C. falcicauda Bastin, Burckhardt & Ouvrard sp. nov., Diaphorina gonzalezi Bastin, Burckhardt & Ouvrard sp. nov., Drepanoza canariensis Bastin, Burckhardt & Ouvrard sp. nov., D. fruticulosi Bastin, Burckhardt & Ouvrard sp. nov., D. molinai Bastin, Burckhardt & Ouvrard sp. nov., Euphyllura confusa Bastin, Burckhardt & Ouvrard sp. nov., Percyella benahorita Bastin, Burckhardt & Ouvrard sp. nov., P. canari Bastin, Burckhardt & Ouvrard sp. nov., P. gomerita Bastin, Burckhardt & Ouvrard sp. nov., P. guanche Bastin, Burckhardt & Ouvrard sp. nov., Strophingia canariensis Bastin, Burckhardt & Ouvrard sp. nov. and S. paligera Bastin, Burckhardt & Ouvrard sp. nov. Arytaina insularis Loginova, 1976, stat. nov. is elevated from a subspecies of A. devia Loginova, 1976 to species rank. Five new combinations are proposed: Drepanoza fernandesi (Aguiar, 2001) comb. nov., D. lienhardi (Burckhardt, 1981) comb. nov., D. montanetana (Aguiar, 2001) comb. nov., D. pittospori (Aguiar, 2001) comb. nov. and Lauritrioza laurisilvae (Hodkinson, 1990) comb. nov., all transferred from Trioza. The hitherto unknown last-instar immatures are described for Megadicrania tecticeps Loginova, 1976, Cacopsylla atlantica (Loginova, 1976) and Lauritrioza laurisilvae (Hodkinson, 1990). We also report Agonoscena targionii (Lichtenstein, 1874) for the first time from the Canary Islands. Our review increases the number of known psyllid taxa from the Canary Islands to 24 genera and 62 species (one of which remains undescribed). Endemism, host plant relationships and biogeographic patterns are discussed. Keys for the identification of adults and immatures are provided, as well as information on host plants, distribution and predators.